Development of nanocomposites heat sink (MWCNTs/Cu) using powder injection moulding for electronic applications - ., Ali S Muhsan, Faiz Ahmad (2011)
A fabrication of high performance heat sink composite material made of copper matrix reinforced by multiwalled carbon nanotubes (MWCNTs) up to 2.5 Vol.% using powder injection molding technique (PIM) has been done successfully. A mixture of Cu/MWCNTs was compounded using a Z-blade mixer for homogenous dispersion of solids in the binder. The flow properties were measured using a capillary rheometer in the shear rate range which expected to occur during metal injection molding.